Rest-Phase Hypothermia Reveals a Link Between Aging and Oxidative Stress: A Novel Hypothesis - Zagkle, Elisavet; Grosiak, Marta; Bauchinger, Ulf; Sadowska, Edyta T. (Frontiers in Physiology, 2020)
In endotherms, growth, reproduction and survival are highly depended on energy metabolism. Maintenance of constant body temperature can be challenging for endotherms under continuously changing environmental conditions, such as low or high ambient temperatures or limited food. Thus, many birds may drop body temperature below normothermic values during the night, known as rest-phase hypothermia, presumably to decrease energy metabolism. Under the assumption of the positive link between aerobic metabolism and reactive oxygen species, it is reasonable to suggest that low body temperature, a proxy of energy metabolism, will affect oxidative stress of the birds. Aging may considerably affect behavior, performance and physiology in birds and still requires further investigation to understand age-specific changes along the lifespan of the organism. Until today, age-specific rest-phase hypothermic responses and their effect on oxidant-antioxidant status have never been investigated. We exposed 25 zebra finches (Taeniopygia guttata) of three age classes, twelve young birds (1.1 - 1.3 years old), eight middle-aged (2.4 - 2.8 years old), and five old birds (4.2 - 7.5 years old) to day-long food deprivation or provided them normal access to food under thermoneutral conditions. We compared night-time body temperature, measured through implanted data loggers, and quantified plasma oxidative status (uric acid, antioxidant capacity and d-ROM assay) the following morning. We found age-related differences in night-time body temperature following a day-long food deprivation while all three age groups remained normothermic in the night following a day with access to food. The lowest minimum body temperature (LSM ± SE: 36.6 ± 0.2 °C) was observed in old individuals during rest-phase hypothermia. Surprisingly, these old birds also revealed the highest levels of plasma oxidative damage, while young and middle-aged birds maintained higher night-time body temperature and showed lower values of oxidative damage. These results lead us to propose a novel hypothesis on how aging may lead to an accumulation of oxidative damage; the impaired physiological capacity to thermoregulate with advancing age does increase the risk of oxidative stress under challenging conditions. When energy is limited, the risk to encounter oxidative stress is increasing via a compensation to defend normothermic body temperatures.